2023
DOI: 10.1097/cce.0000000000000834
|View full text |Cite
|
Sign up to set email alerts
|

Patient, Operator, and Procedural Characteristics of Guidewire Retention as a Complication of Vascular Catheter Insertion

Abstract: OBJECTIVES: Guidewire retention after intravascular catheter insertion is considered a "never event. " Prior reports attribute this complication to various characteristics including uncooperative patients, operator inexperience, off-hour or emergent insertion, and underutilization of ultrasound guidance. In this descriptive analysis of consecutive events, we assessed the frequency of patient, operator, and procedural factors in guidewire retention. DESIGN:Pre-specified observational analysis as part of a quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Guidewire loss is a very rare complication of central venous catheterization (CVC), typically considered a “never event”, but it still occurs at a frequency of 0.05%. 3 Complete loss of the guidewire is usually asymptomatic, as observed in this case, but can lead to fatal complications, such as cardiac tamponade, blood vessel perforation, and dysrhythmia. 8 The retained guidewire is usually detected during a procedure, but there have been cases where a diagnosis was discovered incidentally several months later during routine radiology diagnostics.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Guidewire loss is a very rare complication of central venous catheterization (CVC), typically considered a “never event”, but it still occurs at a frequency of 0.05%. 3 Complete loss of the guidewire is usually asymptomatic, as observed in this case, but can lead to fatal complications, such as cardiac tamponade, blood vessel perforation, and dysrhythmia. 8 The retained guidewire is usually detected during a procedure, but there have been cases where a diagnosis was discovered incidentally several months later during routine radiology diagnostics.…”
Section: Discussionmentioning
confidence: 74%
“…Despite improvements in institutional security protocols and standards, the use of anesthesia in uncooperative patients, and the implementation of ultrasound guidance, guidewire retention still occurs in the healthcare system. 3 Contrary to previous reports, the observational study by Kassis et al on 24 guidewire retention incidents found that most cases occurred in non-obese, non-coagulopathic patients during regular shift hours, in the jugular vein position, using ultrasound by attending physicians with preprocedural sedation in non-emergent settings. This suggests that despite improved security protocols and technological advancements in CVC placement, such as the use of ultrasound, human error remains a significant factor.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations